Международный опыт лечения пациентов с генерализованной меланомой кожи - Зайчук, В.В. (Онкологія, 2015)
Modern data are analyzed about morbidity by the skin melanoma (SМ) in the diff erent regions of the world, death rate from this tumor; results of researches of molecular profi le of SМ and features of adjusting of immune answer at its development. The actual going is considered near treatment at generalized SМ; results of clinical tests, presented in 2014–2015 years, and preclinical researches grounding new targets for target and immunotherapy of SМ